Popular Sovereignty in Islamic Law Perspective - al-Shamari, Nayef bin Nahar (Faculty of Sharia and Law, Universitas Islam Negeri (UIN) Walisongo Semarang, 2024)
Popular sovereignty is a fundamental principle in a modern state. The study addresses the noted contradiction between Islam and democracy resulting from the concept of legislative sovereignty. This stems from the Islamic belief in the sovereignty of God Almighty, while democracy places sovereignty in the hands of the people. The core objective of this research is to reconcile the dispute related to sovereignty and to elucidate the relationship between legitimate sovereignty in Islamic and democratic contexts. Both analytical and descriptive methodologies were applied to align with the research’s requirements. The study’s findings reveal that sovereignty has taken various forms since ancient times, and one of these forms aligns with Islamic principles. Consequently, the study recommends a re-evaluation of traditional perspectives on democratic sovereignty, urging recognition of the diverse manifestations of sovereignty.